PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR KOMPLEKS KELAS X SMA NEGERI 6 MAKASSAR: THE EFFECT OF PROBLEM-BASED LEARNING MODEL ON THE WRITING SKILL OF COMPLEX PROCEDURE TEXT IN CLASS X SMA NEGERI 6 MACASSAR - Indawati, Ikha; Usman; Haliq, Abdul (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study aims to describe the writing skills of complex procedure text of Class X SMA Negeri 6 Makassar students before using the problem-based learning model, describe the writing skills of Class X SMA Negeri 6 Makassar students after using the problem-based learning model, and test the effect of using the problem-based learning model on the learning outcomes of writing complex procedure text of Class X SMA Negeri 6 Makassar students. This research is a type of Quantitative research. The research design used is One Group Pretest-Posttest Design. The results of data analysis show that the learning outcomes of learning to write complex procedure texts of Class X SMA Negeri 6 Makassar students before using the problem-based learning model are categorized as less skilled with an average score of 43.9394, the learning outcomes of writing complex procedure texts of Class X SMA Negeri 6 Makassar students after using the problem-based learning model are categorized as quite skilled with an average score of 72.1212; (3) the results of hypothesis testing show that the sig. (2-tailed) value of 0.000 <0.05, so that the alternative hypothesis (Ha) is accepted, namely there is an effect of using problem-based learning on the learning outcomes of writing complex procedure texts of Class X SMA Negeri 6 Makassar students.